(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In colloquial language, the words ’government’ and ’governance’ are used as synonyms, but in the terminology of political science there is a big difference between the two. The meaning of the word governance is much broader than government. Government is a machinery and institutional arrangement that exercises sovereign power to fulfill the external interests of the community, while the process of taking authorized decisions for the benefit of the community and implementing the decisions is called governance.